Infective endocarditis in intravenous drug abusers: an update - Sousa, Cláudia (2012)
Infective endocarditis despite advances in diagnosis remains a common cause of hospitalization, with high morbidity and mortality rates. Through literature review it is possible to conclude that polymicrobial endocarditis occurs mainly in intravenous drug abusers with predominance in the right side of the heart, often with tricuspid valve involvement. This fact can be associated with the type of drug used by the patients; therefore, knowledge of the patient's history is critical for adjustment of the therapy. It is also important to emphasize that the most common combinations of organisms in polymicrobial infective endocarditis are: Staphylococcus aureus, Streptococcus pneumonia and Pseudomonas aeruginosa, as well as mixed cultures of Candida spp. and bacteria. A better understanding of the epidemiology and associated risk factors are required in order to develop an efficient therapy, although PE studies are difficult to perform due to the rarity of cases and lack of prospective cohorts.